(untitled) (Communications in Computational Physics, 2023)
The immersed boundary method has emerged as an efficient approach for the simulation of finite-sized solid particles in complex fluid flows. However, one of the well known shortcomings of the method is the limited support for the simulation of light particles, i.e. particles with a density lower than that of the surrounding fluid, both in terms of accuracy and numerical stability. Although a broad literature exists, with several authors reporting different approaches for improving the stability of the method, most of these attempts introduce extra complexities and are very costly from a computational point of view. In this work, we introduce an effective force stabilizing technique, allowing to extend the stability range of the method by filtering spurious oscillations arising when dealing with light-particles, pushing down the particle-to-fluid density ratio as low as 0.04. We thoroughly validate the method comparing with both experimental and numerical data available in literature.